Tangible Query Interfaces: Physically Constrained Tokens for Manipulating Database Queries. - Ullmer, Brygg.; Ishii, Hiroshi.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
We present a new approach for using physically constrained tokens to express, manipulate, and visualize parameterized database queries. This method extends tangible interfaces to enable interaction with large aggregates of information. We describe two interface prototypes that use physical tokens to represent database parameters. These tokens are manipulated upon physical constraints, which map compositions of tokens onto interpretations including database queries, views, and Boolean operations. We propose a framework for "token + constraint" interfaces, and compare one of our prototypes with a comparable graphical interface in a preliminary user study.